Connections between pension 65 and elderly poverty: Peru 2012-2018 - Orco Díaz, Alipio (2020)
Objective: Determine the relationship of the Pension 65 Program with the level of elderly poverty in Peru: period 2012-2018. Method: The research was of a non-experimental and longitudinal quantitative type; descriptive, correlational and explanatory scope. The population studied was the elderly people in poverty situation, Pension 65 program beneficiaries and who were included in the National Household survey (ENAHO) in the period 2012 – 2018. Results: It demonstrated that Pension 65 program beneficiaries had a 11% more of probability, to get out of poverty compare to older adults who do not receive Pension 65; the house head by women has 0,34% more of probability to be poor related to the houses head by men; live in the urban areas reduces the probability of being poor in 19.4%, compare to those who live in the rural areas. an increase in one year of age increases the probability of being poor in 0,27%, keeping the other variables constant; an additional level of education reduces the probability of being poor in 11% respect from the previous level. Conclusions: The non-contributory pension program, Pension 65, is an effective and efficient public policy to reduce the level of poverty and vulnerability in elderly in Peru.